Allele-specific DNA hypomethylation characterises FSHD1 and FSHD2. Issue 5 (1st February 2016) - Calandra, Patrizia; Cascino, Isabella; Lemmers, Richard J L F; Galluzzi, Giuliana; Teveroni, Emanuela; Monforte, Mauro; Tasca, Giorgio; Ricci, Enzo; Moretti, Fabiola; van der Maarel, Silvère M; Deidda, Giancarlo
Abstract : Background: Facioscapulohumeral muscular dystrophy (FSHD) is associated with an epigenetic defect on 4qter. Two clinically indistinguishable forms of FSHD are known, FSHD1 and FSHD2. FSHD1 is caused by contraction of the highly polymorphic D4Z4 macrosatellite repeat array on chromosome 4q35. FSHD2 is caused by pathogenic mutations of the SMCHD1 gene. Both genetic defects lead to D4Z4 DNA hypomethylation. In the presence of a polymorphic polyadenylation signal (PAS), DNA hypomethylation leads to inappropriate expression of the D4Z4-encoded DUX4 transcription factor in skeletal muscle. Currently, hypomethylation is not diagnostic per se because of the interference of non-pathogenic arrays and the lack of information about the presence of DUX4-PAS. Methods: We investigated, by bisulfite sequencing, the DNA methylation levels of the region distal to the D4Z4 array selectively in PAS-positive alleles. Results: Comparison of FSHD1, FSHD2 and Control subjects showed a highly significant difference of methylation levels in all CpGs tested. Importantly, using a cohort of 112 samples, one of these CpGs (CpG6) is able to discriminate the affected individuals with a sensitivity of 0.95 supporting this assay potential for FSHD diagnosis. Moreover, our study showed a relationship between PAS-specific methylation and severity of the disease. Conclusions: These data point to the CpGs distal to the D4Z4 array as a critical region reflecting multiple factors affecting the epigenetics of FSHD. Additionally, methylation analysis of this region allows the establishment of a rapid and sensitive tool for FSHD diagnosis.